KEKUATAN NILAI SOSIAL KEHIDUPAN MASYARAKAT DALAM PERSPEKTIF PELAKSANAAN SYARIAT ISLAM MELALUI TINJAUAN PERATURAN BUPATI NOMOR 5 TAHUN 2010 DI ACEH BARAT - Nellis Mardhiah (Universitas Teuku Umar, 2018)
The policy of PERBUP Number 5 of 2010 declaring a manifestation of the policy process that focuses on the application of Islamic fashion in enforcing Islamic law in Aceh Barat District. This study the research her had used is a qualitative approach with the Incremental theoretical analysis that the success of the policy is very large in relation to the policy formulation process for creating the success in its implementation. The results obtained are: the implementation of the rules of PERBUP reflects peoples participation in the development of social policy, one of them wears Islamic dress codes according to the rules of Islam, considering the policy of Islamic law as one of the special autonomy in the province, can prevent immoral acts that against the rules of the code of ethics of Islamic among the people of Aceh in general and particularly among people in West Aceh. The conclusion of this study is the policy of Islamic law in west Aceh district that has been prescribed in the regulations as Regent can show the strength values that will be established in west Aceh district in enforcing Islamic law in the area of Sufism faith (Tauhid Tasawuf).Keywords: Strength, Islamic Law, Social Value